2015
DOI: 10.1108/emjb-10-2013-0053
|View full text |Cite
|
Sign up to set email alerts
|

Impact of trust on the relationship of e-service quality and customer satisfaction

Abstract: Purpose – The purpose of this paper is to find the role of trust as a mediating variable between e-service quality and customer satisfaction in internet banking. Design/methodology/approach – The paper opted for an exploratory study using closed ended questionnaire. The empirical data are drawn from 367 customers of internet banking. Factor structure of e-SQ, customer satisfaction and trust has been tested using EFA and CFA by gap values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 100 publications
11
88
1
6
Order By: Relevance
“…The study reveals that e-SQ was found to be strongly correlated with customer satisfaction (Kundu and Datta, 2015). The results confirm trust as a mediating variable between e-service quality while analysing the same model with gap value and perception value.…”
Section: Introductionsupporting
confidence: 73%
“…The study reveals that e-SQ was found to be strongly correlated with customer satisfaction (Kundu and Datta, 2015). The results confirm trust as a mediating variable between e-service quality while analysing the same model with gap value and perception value.…”
Section: Introductionsupporting
confidence: 73%
“…Notably, any customer not using e-banking products and services was discarded from the study. This study used sample size was 450 and this sample size consistent with e-banking related studies (e.g., Al-Hawari, 2014; Kundu & Datta, 2015).…”
Section: Samplementioning
confidence: 62%
“…While the service quality has become necessary in e-banking (Santos, 2003;Al-Hawari & Ward, 2006), customer satisfaction of e-banking is also a critical issue due to the intensive competition in the banking industry (Herington & Weaven, 2009;Gounaris, Dimitriadis & Stathakopoulos, 2010;Kassim & Abdullah, 2010;Ankit, 2011;Chen, Hsiao & Hwang, 2012;Ganiyu, Uche & Elizabeth, 2012;Thusyanthy, 2014;Kundu & Datta, 2015;Karunakaran & Thusyanthy, 2016).…”
Section: H1mentioning
confidence: 99%
“…The monitoring of access to public services and the collection of information is necessary for real-time to obtain results that are always up to date and ready to direct choices. It has been shown that the exchange of information also on the quality of services helps both to change perceptions and to increase the reading capacity of stakeholders end politicians (Glatzer, 2015;Kundu & Datta, 2015;AL Athmay et al, 2016). Furthermore, it seems to be able to direct the choice of active mobility by the ease of access to public administration services without taking into account the trend and the general perception given by the regional indicators of the different regions.…”
Section: Discussionmentioning
confidence: 99%